Implementation of Cross-Cultural Counseling in Bridging Differences in Multicultural Communities - Nurhafiza, Nurhafiza; Jarnawi, Jarnawi; Duri, Rofiqa (JASNA : Journal For Aswaja Studies, 2024)
In the context of Indonesia and Malaysia, where cultural diversity is a very rich characteristic, the implementation of cross-cultural counseling utilization can be an effective means to strengthen social harmony and reduce the potential for conflict or tension between cultures. Therefore, research on the role of cross-cultural counseling in bridging the differences in multicultural societies in these two countries is very relevant and important to do. This research is a qualitative research using a field study approach using data collection techniques and a combination of survey analysis, in-depth, focus group discussions (FGD), and documentation study analysis. The results of the study indicate that cross-cultural counseling plays an important role in bridging differences in multicultural societies between Indonesia and Malaysia. Through cultural understanding of cross-cultural counseling activities carried out between counselors and clients with different cultures and paying attention to their diversity, cross-cultural guidance and counseling can help these two countries in bridging various differences in multicultural societies to understand, appreciate intercultural interactions